Analisis Likuiditas Laporan Keuangan Perusahaan Dagang Dalam Zahir Accounting Versi 5.1 - M.L.Dian Ela Revita; Indah Ariyati (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2020)
Abstack  Decision making is the most important thing in managing a company. Errors in decision making can result in losses, which in turn the company will suffer losses. Loss prevention is to conduct an analysis of financial statements in accordance with accounting principles. By analyzing the financial statements, management is expected to be able to assess the company's financial condition, so that it is easy to understand, so that the financial decisions made can be in accordance with the company's financial weaknesses and strengths. In microeconomics, one of the goals of a company is maximizing corporate profits. The use of Zahir Accounting Program version 5.1 can help the management of the Salsabila Mart Bekasi trading company in analyzing financial statements as a benchmark for decision making. The liquidity analysis obtained from the Zahir Accounting application calculation shows that Salsabila Mart Bekasi in June 2019 was able to settle short-term debt from current assets owned by the company. From all aspects of calculated liquidity, this shows that Salsabila Mart Bekasi is a highly liquid company, with an average liquidity yield Current Ratio: 36,639.41%; Qucik Ratio: 23,351.44% and Cash Ratio: 22,551.44%. Current assets are still far more than current liabilities that must be fulfilled during June. In this research the Zahir Accounting Version 5.1 application can help the company's internal and external parties obtain financial reports and analysis of financial statements as information used in making managerial decisions. Keywords: Liquidity Analysis, Financial Statements, Zahir Accounting